Modeling Atlantic herring distribution in the Northeast Atlantic for informed decision-making towards sustainable fisheries - Standaert, Ward; Musimwa, Rutendo; Stevens, Martha; Guerra, Jesus Alonso; Muñiz, Carlota; Debusschere, Elisabeth; Pint, Steven; Everaert, Gert (Frontiers in Marine Science, 2024)
The withdrawal of the United Kingdom from the European Union will likely result in reduced fishing grounds for the Belgian fishing fleet. This fleet now targets demersal fish, but there used to be a tradition of catching Atlantic herring (Clupea harengus). After the stock collapse of Atlantic herring in the 1970s, fishing on herring by the Belgian fleet did not recover and herring quotas are now exchanged with the Netherlands and Germany. To assess the feasibility of reintroducing herring fisheries for the Belgian fishing fleet, our study created spatiotemporal species distribution models for Atlantic herring in the Northeast Atlantic Ocean, focusing results on the Belgian Part of the North Sea. In total 30078 occurrence records were derived and processed to fit species-environmental relationships with temperature, salinity, seabed characteristics and plankton concentration using Maximum entropy (Maxent) models. The Area Under the Curve of the Receiver Operating Characteristic plot (AUC) and the True Skill Statistic (TSS) were used to assess model fit. Models performed well (AUC > 0.7 and TSS > 0.6). While a broad spatiotemporal distribution of Atlantic herring in the Northeast Atlantic Ocean was inferred, regional differences show that herring habitat is most suitable during winter months in the Belgian Part of the North Sea for both adult and larval herring (habitat suitability index > 75 %). This regional trend in the Belgian Part of the North Sea was negatively correlated (R = -0.8) with the North Atlantic Oscillation (NAO). We anticipate that these findings will provide valuable insights for policymakers to implement sustainable fisheries management practices.